2003
DOI: 10.1089/154099903322404339
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Women's Decisions to Seek Treatment for Urinary Incontinence

Abstract: Less than half of community-dwelling adult U.S. women with symptoms of urinary incontinence have talked with a physician about urinary incontinence. In addition to duration of symptoms, factors associated with treatment seeking included the impact of incontinence on quality of life, lack of embarrassment about talking to a physician about urinary symptoms, and attitudes toward healthcare use. Concerns about the meaning of incontinence for overall and future health were important reasons for women choosing to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
250
4
9

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(277 citation statements)
references
References 28 publications
14
250
4
9
Order By: Relevance
“…In other similar study, the reported prevalence was 21.87%. [13][14][15] Prevalence of various types of incontinence in our studies, were similar to the study conducted by Kumari et al, who reported the overall prevalence of UI as 12%, among whom 46% had stress incontinence, 26% had urge, and 28% had mixed type. 14 In another study, the prevalence of stress, mixed, and urge type was 16.13%, 3.67%, and 2.07%, respectively.…”
Section: Discussionsupporting
confidence: 90%
“…In other similar study, the reported prevalence was 21.87%. [13][14][15] Prevalence of various types of incontinence in our studies, were similar to the study conducted by Kumari et al, who reported the overall prevalence of UI as 12%, among whom 46% had stress incontinence, 26% had urge, and 28% had mixed type. 14 In another study, the prevalence of stress, mixed, and urge type was 16.13%, 3.67%, and 2.07%, respectively.…”
Section: Discussionsupporting
confidence: 90%
“…The reason for the lack of care seeking in Ն50% of women with incontinence [5][6][7][8] remains puzzling, as the majority of women in our study understood that inherent difficulties with their pelvic floor or bladder contributed to their incontinence. It may be that even though women understand that damage to the pelvic floor or bladder is related to UI, they are not aware that effective treatments exist when this damage has occurred.…”
Section: Figmentioning
confidence: 99%
“…3,4 Despite these effects, half or fewer of women with incontinence discuss their UI with a healthcare provider. [5][6][7][8] Even when healthcare providers are consulted, there are surprisingly low rates of treatment of women with leakage symptoms. 5,9,10 Studies on why women do not seek treatment for UI have identified potential reasons, such as embarrassment, viewing it as a normal part of aging, feeling that they can cope on their own, and having low expectations of benefit from treatment.…”
mentioning
confidence: 99%
“…23,24 Most of other studies in which stress insentience was commonest type. 25,26 In our study, the total prevalence of OAB was 39%. Of these 50.1% (176) reported that their sexual life is spoilt by OABS, 16.8% (59) of the women had to restrict their daily activities, 37.0% (130) reported their OABS affected their physical activities and 54.4% (191) said they affected their social life.…”
mentioning
confidence: 46%